Umbilical Cord Blood-Derived CD34+ Cells Improve Outcomes of Traumatic Brain Injury in Rats by Stimulating Angiogenesis and Neurogenesis. Issue 8 (August 2014) - Chen, Sheng-Hsien; Wang, Jhi-Joung; Chen, Chung-Hwan; Chang, Hsiu-Kang; Lin, Mao-Tsun; Chang, Fong-Ming; Chio, Chung-Ching
Human umbilical cord blood cells (HUCBCs) have been shown to be beneficial in reducing neurological deficits in rats with brain fluid percussion injury (FPI). This study aimed to assess the basic mechanisms underlying the neuroprotective effects of HUCBC-derived cluster of differentiation 34-positive (CD34 + ) cells. Rats were divided into three major groups: (i) sham-operated controls; (ii) FPI rats treated with phosphate-buffered saline (PBS); (iii) FPI rats treated with 0.2%, 50%, or 95% CD34 + cells (in 5 × 10 5 cord blood lymphocytes and monocytes). Intravenous (IV) administration of 0.3 ml of PBS, 0.2% CD34 + cells, 50% CD34 + cells, or 95% CD34 + cells was conducted immediately after FPI. It was found that 4 days post-FPI, CD34 + cells could be detected in the ischemic brain tissues for 50% CD34 + cell- or 95% CD34 + cell-treated FPI rats, but not for the PBS-treated FPI rats or the 0.2% CD34 + cell-treated FPI rats. CD34 + cell (0.2%)-treated FPI rats or PBS-treated FPI rats displayed neurological and motor deficits, cerebral contusion and apoptosis [e.g., increased numbers of both TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling)-positive cells and caspase-3-positive cells], and activated inflammation (e.g., increased serum levels of tumor necrosis factor-α). FPI-induced neurological motor dysfunction, cerebral contusion and apoptosis, and activated inflammation could be attenuated by 50% CD34 + or 95% CD34 + cell therapy. In addition 50% or 95% CD34 + cell therapy but not PBS or 0.2% CD34 + cell therapy significantly promoted angiogenesis (e.g., increased numbers of both vasculoendothelial growth factor-positive cells and 5-bromodeoxyuridine (BrdU)-endothelial double-positive cells), neurogenesis (e.g., increased numbers of both glial cell line-derived neurotrophic factor-positive cells and BrdU/neuronal nuclei double-positive cells) in the ischemic brain after FPI, and migration of endothelial progenitor cells from the bone marrow. Our data suggest that IV administration of HUCBC-derived CD34 + cells may improve outcomes of FPI in rats by stimulating both angiogenesis and neurogenesis.